HUBUNGAN ANTARA FREKUENSI KEDATANGAN IMAGO ERIONOTA THRAX PADA BUNGA PISANG DAN KETERJADIAN PENYAKIT LAYU BAKTERI PISANG PADA LAHAN SAWAH, TEGALAN DAN PEKARANGAN - Radix Suharjo, Siti Subandiyah ,dan Edhi Martono . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2008)
Relationship Between Arrival Frequency of Erionota thrax to the Banana’s Flower and Disease Incidence of Banana Bacterial Wilt in Wet Rice Field, Dry Field and House Yard. This research was conducted in the Sub District of Samigaluh, Kulon Progo and Laboratory of Bacteriology, Plant Protection Department, Faculty of Agriculture, Gadjah Mada University, Yogyakarta December 2002 to June 2003. The aim of this research was to investigate relationship between arrival frequency of Erionota thrax to the banana’s flower and disease incidence of Banana Bacterial Wilt in the three diffrent land uses (wet rice field, dry field and house yard). A survey method was done in this research. Stratified purpossive sampling was performed to collect the data. Strata used were wet rice field, dry field and house yard. Observation of the arrival frequency of E. thrax was done to the flowering banana. Data that collected in this study were disease incidence of Banana Bacterial Wilt and arrival frequency of E. thrax to the banana’s flower. The data was analized with Correlation test using SPSS 11.5 for windows with 5% of significant level. The results showed that the arrival frequency of imago E. thrax to the banana’s flower per one flowering seasons (5 days) were 17.65 imago (wet rice field), 15,65 imago (dry field) and 11 imago (house yard). Meanwhile, the disease insidence of Banana Bacterial wilt in the three different land uses were 5.41% (wet rice field), 3.81% (dry field) and 7.10% (house yard). Correlation analysis showed that there was no relationship between arrival frequency of E. thrax to the banana’s flower and the disease insidence of Banana Bacterial Wilt in the three different land uses. Its means that the arrival frequency of E. thrax to the banana’s flower did not influence the disease incidence of banana bacterial wilt in those areas.